A study on the impact of Internet use on depression among Chinese older people under the perspective of social participation - Hua-lei Yang; Shuo Zhang; Si-meng Cheng; Zhi-yun Li; Yuan-yang Wu; Si-qing Zhang; Jia-hao Wang; Yi-wen Tao; Yi-dan Yao; Lin Xie; Wen-jing Xiao; Xiao-qing Tang; et al. (BMC Geriatrics, 2022)
Abstract Purpose This study aimed to evaluate the role of social participation in the relationship between internet use and depressive symptoms among Chinese older adults and investigate how the internet use interact with social participation to reduce the risk of depressive symptoms. Methods Based on the survey from the China Health and Retirement Longitudinal Study (CHARLS) in 2018, we identified 4645 subjects and used the Ordinary Least Square method (OLS) and Propensity Score Matching method (PSM) to identify the association between Internet use and depression of older people, and further test how social participation played a role in the relationship. Results The level of depression of older people was significantly reduced in those who using internet in China, and the effect was still robust under different identification methods. The mental health was improved when using internet because of the increase of social participation and social capital. Further, The positive effect was stronger especially in those who were female, living in rural areas, has low education attainments and were 70–79 years old. Conclusions The popularity of internet use has a positive effect on the depressive symptoms of Chinese older adults. Effective measures were encouraged to improve the friendliness of internet for older people and promote the popularization of the Internet and older group, achieving the spiritual well-being of them in the Internet society.